Glanzmann’s Thrombasthenia: Identification of 19 New Mutations in 30 Patients - D’Andrea, Giovanna; Colaizzo, Donatella; Vecchione, Gennaro; Grandone, Elvira; Di Minno, Giovanni; Margaglione, Maurizio; the GLAnzmann’s Thrombasthenia Italian Team (GLATIT); on behalf of (Thrombosis and Haemostasis, 2002)
Glanzmann’s thrombasthenia (GT) is a genetically heterogeneous autosomal recessive syndrome associated with a bleeding tendency. To elucidate molecular basis of GT we have screened for mutations 30 GT patients. On the whole, 21 different candidate causal mutations, 17 in the αIIb and 4 in the β3 gene have been found. Only two (αIIb Pro145Ala and IVS3(−3)-418del) have been previously reported. Nine mutations (42.9%) were likely to produce truncated proteins, whereas the remaining 12 were missense mutations that affected highly conserved residues in αIIb and β3 genes. Six mutations were found in different patients suggesting a possible founder effect. The wide spectrum of expressivity, ranging from mild to severe also among patients carrying the same mutations, provided evidence for a role of different loci or circumstantial factors. In conclusion, we have identified a spectrum of unreported mutations that may be of value to unravel the role of specific regions of αIIb and β3 genes.
Keywords: Glanzmann’s Thrombasthenia; αIIb and β3 genes; mutations